A study on factors influencing the adoption of electronic payment / Nashroy Andryan Nurali - Nurali, Nashroy Andryan (2014)
The purpose of this research is to study the factors influencing the adoption of e-payment among tax payer in Kota Kinabalu City. The factors will be trust, benefits and safety of e-payment. Thus, there were 384 respondents selected by the researcher to be the sample size on this research. From the findings, it will explain what the main factors that will influence the adoption of electric payment. Apart from that, relationship and reliability of variables will be explained to know what variables has strong relationship with dependent variable and to test the hypothesis constructed.